Pengaruh Perbedaan Konsentrasi KCI Terhadap Karakterisitik Refined Karagenan dari Rumput Laut (Euchema Spinosum) - Devi arianty; Siti Halija; Ulfatul Mardiyah (Faculty of Science and Technology University Ibrahimy, 2025)
Eucheuma spinosum is a seaweed that produces refined carrageenan, a type of carrageenan that has been processed and purified to remove impurities and non-carrageenan components, resulting in a product with higher purity and better quality. Refined carrageenan is generally used in various products in the food and cosmetic industries as a thickener, stabilizer, and gelling agent. The study aims to determine the effect of KCl precipitation solution on the yield, pH, moisture content, and ash content of refined carrageenan from Eucheuma spinosum seaweed. This study used a completely randomized design with three KCl concentrations: 1%, 1.25%, and 1.5%. The stages of refined carrageenan production included washing, soaking in a 0.15% KOH solution, rinsing with water until reaching a neutral pH, extraction, precipitation for 30 minutes with KCl solution at various concentrations, filtration, and drying in an oven at 70°C for 48 hours.The results showed that the highest yield was obtained with the 1.5% KCl treatment, which was 6.23%, while the best results for pH, ash content, and moisture content were found at the 1% KCl concentration, with values of 6.30, 20.07%, and 4.55%, respectivelys.